A comprehensive experimental investigation of combustion and heat release characteristics of a biodiesel (hazelnut kernel oil methyl ester) fueled direct injection compression ignition engine - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
In the present study, hazelnut (Corylus avellana L.) kernel oil was transesterified with methanol using potassium hydroxide as catalyst to obtain biodiesel and a comprehensive experimental investigation of combustion (cylinder gas pressure, rate of pressure rise, ignition delay) and heat release (rate of heat release, cumulative heat release, combustion duration and center of heat release) parameters of a direct injection compression ignition engine running with biodiesel and its blends with diesel fuel was carried out. Experiment parameters included the percentage of biodiesel in the blend, engine load, injection timing, injection pressure, and compression ratio. Results showed that hazelnut kernel oil methyl ester and its blends with diesel fuel can be used in the engine without any modification and undesirable combustion and heat release characteristics were not observed. The modifications such as increasing of injection timing, compression ratio, and injection pressure provided significant improvement in combustion and heat release characteristics. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biodiesel; Hazelnut kernel oil methyl ester; Diesel engine; Combustion; Heat release; VEGETABLE-OIL; PALM OIL; DIESEL; EMISSIONS; PERFORMANCE; JATROPHA; KARANJA; MODEL